Anti-inflammatory and antioxidant activity of astragalus polysaccharide in ulcerative colitis: A systematic review and meta-analysis of animal studies - Hu, Heng-Chang; Zhang, Wei; Xiong, Pei-Yu; Song, Li; Jia, Bo; Liu, Xing-Long (Frontiers in Pharmacology, 2022)
Background: Accumulated evidence indicates that astragalus polysaccharide (APS) may have a beneficial impact on ulcerative colitis (UC) by suppressing inflammation and decreasing oxidative stress. Nevertheless, the credibility of the evidence for this practice is unclear. Therefore, we intended to conduct a systematic review and meta- analysis of animal studies to assess the anti-inflammatory and antioxidant activity of APS when used in the treatment of UC. Methods: Electronic bibliographic databases including PubMed, EMBASE, Web of Science, Chinese Biomedical Literature (CBM), Wanfang Database, CQVIP Database and China National Knowledge Infrastructure (CNKI) were retrieved for relevant animal studies. The methodological quality of animal studies was evaluated based on the SYstematic Review Center for Laboratory animal Experimentation (SYRCLE’s RoB tool). A meta-analysis was performed according to the Cochrane Handbook for Systematic Reviews of Interventions by using STATA 12.0 software. This study was registered with PROSPERO, number CRD42021272595. Results: Twenty qualified publications involving 591 animals were included in this study. There was a significant association of APS with levels of disease activity index (DAI), colon macroscopic damage index (CMDI), colon histopathologic score (CHS), myeloperoxidase (MPO), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), superoxide dismutase (SOD) and malondialdehyde (MDA) compared with that in the control group. Sensitivity analysis that eliminated one study at each stage did not change these results. Egger’s test and funnel plot showed that publication bias was existed. Conclusions: In this meta-analysis, APS treatment significantly mitigated colonic damage by reducing the levels of MPO, TNF-α, IL-6, IL-1β and MDA and recovering the SOD activity. These results demonstrated a protective role of APS in the treatment of UC and showed that the anti-inflammatory and antioxidant activity were implicated in the underlying mechanisms. Hence, APS may represent a promising candidate for treating UC. However, due to potential publication bias, a cautious interpretation is needed.